Stabilization of Long-Looped i-Motif DNA by Polypyridyl Ruthenium Complexes - Pages, Benjamin J.; Gurung, Sarah P.; McQuaid, Kane; Hall, James P.; Cardin, Christine J.; Brazier, John A. (Frontiers in Chemistry, 2019)
A spectroscopic study of the interactions of Λ- and Δ-[Ru(phen)2(dppz)]2+ with i-motif DNA containing thymine loops of various lengths. In the presence of i-motifs, the luminescence of the Λ enantiomer was enhanced much more than the Δ. Despite this, the effect of each enantiomer on i-motif thermal stability was comparable. The sequences most affected by [Ru(phen)2(dppz)]2+ were those with long thymine loops; this suggests that long-looped i-motifs are attractive targets for potential transition metal complex drugs and should be explored further in drug design.